2014
DOI: 10.5530/phm.2014.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Cefepime and Tazobactam in Injectables by Ultra-High Performance Liquid Chromatography Method

Abstract: Aim: Stability indicating ultra-high performance liquid chromatography (UHPLC) method was developed and validated for the determination of cefepime (CFPM) and tazobactam (TZB) in injectable dosage form. Materials and Methods: Separation was performed in a Dionex Ultimate 3000 UHPLC system equipped with chromeleon software using Acclaim 120 C 18 (250 × 4.6 mm, 5 μm particle size) column with mobile phase (pH 6.0) containing methanol and sodium acetate buffer in the ratio of 11:89 v/v with a fl ow rate of 1.8 mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It is used to treat urinary tract infections, septicemia, staphylococcal infections, bronchitis, intra-abdominal infections, skin and its structures infections, pneumonia infections, and in febrile neutropenic patients (Glish and Burinsky, 2008;Lemke et al, 2002). CFP stability was estimated using several methods using chromatography (Abd El Aziz Shama et al, 2021;Al Kamaly, 2022;Bjergum et al, 2021;De Borba et al, 2008;Dos Anjos et al, 2022;El-Beltagy et al, 2019;El-Dars et al, 2019;Fage et al, 2021;Isla et al, 2005;Jagadeesh Kumar et al, 2010;Jiang et al, 2010;Jiménez Palacios et al, 2005;Kalyani et al, 2018;Kommana et al, 2014;Liu et al, 2018;Mameli et al, 2019;Moorthy et al, 2020;Nemutlu et al, 2009, Ocaña González et al, 2004Ohmori et al, 2011;Patil et al, 2018;Rehm and Rentsch, 2020;Rodrigues et al, 2016;Seraisso et al, 2022;Shrestha et al, 2014;Siddiqui et al, 2010;Sun et al, 2022;Sundara Raj et al, 2013;Sunitha et al, 2013;Van Vooren and Verstraete, 2021;Zander et al, 2015) but these methods had some disadvantages as complex mobile phase composition, increased matrix effect, decreased sensitivity, and inability to identify degradants using trace analysis in addition to fragmentation (Niessen, 2010;Niessen and Ricardo, 2017), less environmentally friendly, and time-consuming. However, there have been no previous analytical procedures of trace analysis reported on CFP stability studi...…”
Section: Introductionmentioning
confidence: 99%
“…It is used to treat urinary tract infections, septicemia, staphylococcal infections, bronchitis, intra-abdominal infections, skin and its structures infections, pneumonia infections, and in febrile neutropenic patients (Glish and Burinsky, 2008;Lemke et al, 2002). CFP stability was estimated using several methods using chromatography (Abd El Aziz Shama et al, 2021;Al Kamaly, 2022;Bjergum et al, 2021;De Borba et al, 2008;Dos Anjos et al, 2022;El-Beltagy et al, 2019;El-Dars et al, 2019;Fage et al, 2021;Isla et al, 2005;Jagadeesh Kumar et al, 2010;Jiang et al, 2010;Jiménez Palacios et al, 2005;Kalyani et al, 2018;Kommana et al, 2014;Liu et al, 2018;Mameli et al, 2019;Moorthy et al, 2020;Nemutlu et al, 2009, Ocaña González et al, 2004Ohmori et al, 2011;Patil et al, 2018;Rehm and Rentsch, 2020;Rodrigues et al, 2016;Seraisso et al, 2022;Shrestha et al, 2014;Siddiqui et al, 2010;Sun et al, 2022;Sundara Raj et al, 2013;Sunitha et al, 2013;Van Vooren and Verstraete, 2021;Zander et al, 2015) but these methods had some disadvantages as complex mobile phase composition, increased matrix effect, decreased sensitivity, and inability to identify degradants using trace analysis in addition to fragmentation (Niessen, 2010;Niessen and Ricardo, 2017), less environmentally friendly, and time-consuming. However, there have been no previous analytical procedures of trace analysis reported on CFP stability studi...…”
Section: Introductionmentioning
confidence: 99%
“…Literature review revealed the reporting of different methods for the estimation of the PPC and TZB drugs either alone, together or in combination with other antibiotics. Several methods were reported for the determination of PPC/TZB [15,16] or CFM/TZB [17,18]. However, only few have been reported for the simultaneous determination of the three drugs under study using HPLC-MS detection in biological fluids [19][20][21][22], and one capillary zone electrophoresis (CZE) method [23].…”
Section: Introductionmentioning
confidence: 99%
“…Cefepime or its content of N-methyl pyrrolidine were also determined by several methods such as HPLC [12,13], MEKC [14,15], GC [16,17], TLC [18,19], ion chromatography [20,21], spectrophotometry [22,23], spectrofluorimetry [24,25], voltammetry [26], capillary electrophoresis [27,28] and chemilluminescence [29].…”
Section: Introductionmentioning
confidence: 99%